Issues in Usul al-Din - Abdullah, Fatimah (IIUM Press, 2009)
The greater challenge to Aqidah at present is no longer revolving around the theological differences of the past but rather around ideological challenges advocated by western thought such as, positivism, secular humanism, liberalism and post-modernism. These ideologies not only threaten the tenets of Islamic belief but more seriously the Islamic doctrine itself. One form of confusion comes from misguided modern pseudo scientific studies such as those that exaggerate the role of heredity in determining ethical human behaviour and conduct. A clear example of this is the studies that claim behaviors like homosexuality and lesbianism are inherited by specific genes. This book in defense of Islam, addresses the emerging contemporary needs using the premises of traditional roots or sources and original terminology with a modernized approach.